Design of ZnO–VSe2 nanocomposite for high performance asymmetric supercapacitors - Danish Arif; Rajwali Khan; Atta Ullah Shah; Kashif Safeen; Khalid M. Alotaibi; Hayat Ullah; Muhammad Zia Ullah Shah; Wubshet Mekonnen Girma; Akif Safeen (Scientific Reports)
Abstract Supercapacitors exhibit limitations such as low energy density, high self-discharge rates, and degradation of electrochemical performance over extended cycling. This study presents the development of a high-performance asymmetric supercapacitor by synthesizing novel ZnO-VSe2 nanocomposites through wet-chemical methods, aiming to enhance capacity, energy density, and durability. The capacitive performance of these materials was systematically evaluated in an aqueous alkaline electrolyte (KOH) at a concentration of 2 M. ZnO-VSe2 composite demonstrates superior electrochemical energy storage capabilities, achieving a specific capacitance of 898 F/g and reducing overall resistance, enabling rapid electrolyte diffusion. These optimized electrochemical characteristics underscore the potential of ZnO-VSe2 for energy storage applications. Specifically, the ZnO-VSe2||AC asymmetric supercapacitor achieved an impressive capacitance of 260 F/g, an energy density of 71 Wh/kg, and a maximum power output of 6948 W/kg, along with a remarkable stability of 89.1% at a current density of 10 A/g over 5000 cycles. The proposed methodology offers a cost-effective and promising approach for evolving high-energy hybrid supercapacitors for energy storage applications.